Users : a novel - Winnette, Colin (Soft Skull Press, 2023)
"Miles, a lead creative at a midsize virtual reality company known for its "original experiences," has engineered a new product called The Ghost Lover. Wildly popular from the outset, the "game" is simple: a user's simulated life is almost identical to their reality, except they're haunted by the ghost of an ex-lover. However, when a shift in the company's strategic vision puts The Ghost Lover at the center of a platform-wide controversy, Miles becomes the target of user outrage, and starts receiving a series of anonymous death threats. Typed notes sealed in envelopes with no postage or return address, these persistent threats push Miles into a paranoid panic, blurring his own sense of reality, catalyzing the collapse of his career, his marriage, and his relationship with his children"--